2018
DOI: 10.1097/txd.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Chronic Lung Allograft Dysfunction Assessed by Biphasic Computed Tomographic Volumetry in Bilateral Living-donor Lobar Lung Transplantation

Abstract: BackgroundEarly diagnosis of unilateral chronic lung allograft dysfunction (CLAD) is difficult because the unaffected contralateral lung functions as a reservoir in bilateral living-donor lobar lung transplantation (LDLLT). We previously reported the usefulness of 133Xe ventilation scintigraphy for detection of unilateral change, but the supply of 133Xe has been stopped globally. The present study aimed to examine the usefulness of inspiratory and expiratory computed tomography (I/E CT) volumetry for detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Until 2016, ventilation scintigraphy with 133 Xe washout imaging was used for the diagnosis of unilateral CLAD after bilateral LDLLT 5 , but the use of 133 Xe was discontinued. As an alternative diagnostic tool, inspiratory and expiratory computed tomography volumetry has been used to detect unilateral CLAD after bilateral LDLLT, but this volumetric method rarely allows the early detection of CLAD 12 . By contrast, our study showed that the perfusion shift in Q-scinti predicts the development of unilateral CLAD from 5 years before the diagnosis of CLAD after bilateral LDLLT.…”
Section: Discussionmentioning
confidence: 99%
“…Until 2016, ventilation scintigraphy with 133 Xe washout imaging was used for the diagnosis of unilateral CLAD after bilateral LDLLT 5 , but the use of 133 Xe was discontinued. As an alternative diagnostic tool, inspiratory and expiratory computed tomography volumetry has been used to detect unilateral CLAD after bilateral LDLLT, but this volumetric method rarely allows the early detection of CLAD 12 . By contrast, our study showed that the perfusion shift in Q-scinti predicts the development of unilateral CLAD from 5 years before the diagnosis of CLAD after bilateral LDLLT.…”
Section: Discussionmentioning
confidence: 99%
“…For a definitive diagnosis of CLAD, blood examinations, chest X-ray, computed tomography of the chest, inspiratory and expiratory computed tomography volumetry, ventilation-perfusion scanning, and electrocardiography were also performed at the same time as the pulmonary function testing. Among these, computed tomography of the chest, inspiratory and expiratory computed tomography volumetry, and ventilation-perfusion scanning were mainly used to exclude other potential causes of a reduced lung function [4,7,12,13]. The six-minute walk test and echocardiography were performed at the same time during the first five years after LT.…”
Section: Postoperative Carementioning
confidence: 99%
“…Measurement of inspiratory and expiratory CT lung volumes can be easily performed and CT volumetry has been shown to differentiate RAS patients from BOS patients due to the strong positive correlation between inspiratory lung CT volumes and TLC [ 20 ]. Computed tomography is particularly useful for detecting CLAD affecting a single lung [ 7 , 21 ], because the unaffected contralateral lung compensates for the deficit in lung function on PFTs. A decrease over time in the difference between inspiratory and expiratory lung volumes has been reported for obstructive and restrictive CLAD phenotypes [ 21 ].…”
Section: Lung Parenchyma Methods: Assessment Of Lung Volume and Attenuation And Their Variations Between Inspiration And Expirationmentioning
confidence: 99%
“…Computed tomography is particularly useful for detecting CLAD affecting a single lung [ 7 , 21 ], because the unaffected contralateral lung compensates for the deficit in lung function on PFTs. A decrease over time in the difference between inspiratory and expiratory lung volumes has been reported for obstructive and restrictive CLAD phenotypes [ 21 ].…”
Section: Lung Parenchyma Methods: Assessment Of Lung Volume and Attenuation And Their Variations Between Inspiration And Expirationmentioning
confidence: 99%
See 1 more Smart Citation